Poverty Commodification of kitabisa.com Crowdfunding Ads in Post Pandemic: A Semiotic Analysis - Zulfa, Indana; Palupi, P (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: The objective of this study is to examine how poverty is represented in the advertising videos of Kitabisa.com and to identify the forms of commodification of poverty portrayed in these advertisements.. Methodology: This study utilizes a qualitative approach, employing semiotic analysis based on Roland Barthes' theory. Results : The findings reveal that Kitabisa.com advertisements commodify poverty by portraying dramatic circumstances through the use of shabby appearances, children and elderly people working, and limited access to education and healthcare. These depictions are designed to elicit sympathy from the audience and encourage them to donate through the platform. Applications/Originality/Value: The analysis further identifies several forms of commodification, including the commodification of content through editing before dissemination and the commodification of audiences by inducing their curiosity and empathy towards the characters, thereby prompting them to donate to the cause. Overall, this research provides valuable insights into how poverty is portrayed and commodified in advertising and sheds light on the broader implications of such representations.